Association between horizontal violence and turnover intention in nurses: A systematic review and meta-analysis - Zhang, Yue; Yin, Rulan; Lu, Jing; Cai, Jianzheng; Wang, Haifang; Shi, Xiaoqing; Mao, Lifen (Frontiers in Public Health, 2022)
Background Horizontal violence is common in nurses. Most published studies have focused on horizontal violence to higher turnover rates in nurses, however, it lacks systematic reviews and meta-analyses. The purpose of this review is to quantitatively assess the correlation between horizontal violence and turnover intention in nurses. Methods A Systematic review and meta-analysis. Four English databases (Cochrane, PubMed, Embase and CINAHL) and three Chinese databases (SinoMed, CNKI and Wanfang) were searched for relevant studies (up to March 6, 2022). The relationship between horizontal violence and turnover intention was evaluated using Fisher’s z value, which was then converted to r. STATA 16.0 was used to perform statistical analysis. Random-effects model was performed to synthesize data. Results A total of 14 studies with 6472 nurses were included. A low positive correlation of horizontal violence with turnover intention was found (pooled r=0.32 [0.29-0.34]). Subgroup analysis showed sample size, quality not be the sources of heterogeneity. Measurement tool was the source of heterogeneity. Although geographic region might not be the sources of heterogeneity, further subgroup analysis of country reveals heterogeneity. Funnel plot and Egger’s test showed no publication bias. Conclusion There was a low positive correlation between horizontal violence and turnover intention in nurses. This finding may cause nursing managers to pay more attention to horizontal violence and reduce the nurse turnover rate. The correlation between horizontal violence and turnover intention is different in countries, which may be related to cultural differences. However, this review lacks sufficient evidence to support it. Researchers are advised to pay attention to the influence of cultural differences on the correlation between horizontal violence and turnover intention.